Analisis Struktur Terowongan Pengelak Pada Bendungan Kualu Kabupaten Toba Samosir Provinsi Sumatra Utara - Afan Allail Rofikha; Suwanto Marsudi; Evi Nur Cahya (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
Diversion structure consists of diversion tunnel and Cofferdam. These two contructions should built in the early construction of the dam, have function to divert the river flow during the period of dam construction. The plans of Kualu dam diversion tunnel designed using horseshoe shape F, upstream of the tunnel at a depth of 41.625 m and upstream elevation + 695.5 m. In this study there was flood routing with Q25th which is 709,331 m 3 /s and obtained using 9 m diameter, then a cofferdam is planned to build as high as 15 m. Based on the calculation of loading and calculated four load combinations, they are : after contruction condition, after contruction under earthquake condition, at the operation time condition, and at the operation time under earthquake condition. From the results of the load combinations, the structure was analyzed using Beggs method and Staad Pro method. These two methods were used to figure the maximum moment of the structure and to determine the needed reinforcement in the tunnel construction. After the analysis, it is noticed that there is a difference position of the maximum moment, this is caused by the support in the Beggs method assumed to be a vertical loads.